PENINGKATAN HASIL BELAJAR SIKLUS AIR MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA KOMIK DI KELAS V - Siti Amalia Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The role of the teacher is one aspect that influences learning outcomes. Learning media is one of the tools needed by the teacher, the media is used to complement the information or material that will be provided. The purpose of developing this media is so that students can easily understand and understand the subject matter that is transmitted during the learning process. One of the problems faced by students, especially at the basic education level, is the difficulty level of students in mastering the subject matter being taught. This is also the background to the problems that arise in the learning process in class V where students have difficulty mastering the material being taught without the help of the media. Therefore a solution is needed, one of which is through the use of media that is able to meet the needs of students in the classroom. Based on the problems that exist, the author aims to improve the learning outcomes of grade 5 students in the water cycle material using comic media, as well as the learning process using problem-based learning models. Data collection techniques were carried out using formative tests, observation and documentation using classroom action research in 3 learning cycles. The results showed that the use of the problem-based learning model with the help of comic media had a significant effect on improving the learning outcomes of grade 5 students as evidenced by the increase in scores obtained by students. Thus it can be concluded that the problem-based learning model with the help of comic media can improve student learning outcomes in the water cycle material in grade 5.